To evaluate the truth of the statements regarding the growth rates of the sequences for \( f(x) = 2 \cdot 2^x \) and \( g(x) = 10x + 2 \), let's analyze the sequences and their growth rates.
The sequence for \( f(x) \) is:
- Term 1: 4
- Term 2: 8
- Term 3: 16
- Term 4: 32
- Term 5: 64
- Term 6: 128
- Term 7: 256
- Term 8: 512
- Term 9: 1024
The sequence for \( g(x) \) is:
- Term 1: 12
- Term 2: 22
- Term 3: 32
- Term 4: 42
- Term 5: 52
- Term 6: 62
- Term 7: 72
- Term 8: 82
- Term 9: 92
Now, let's compare their growth rates:
For \( f(x) \):
- Growth from Term 1 to Term 2: 8 - 4 = 4
- Growth from Term 2 to Term 3: 16 - 8 = 8
- Growth from Term 3 to Term 4: 32 - 16 = 16
- Growth from Term 4 to Term 5: 64 - 32 = 32
- Growth from Term 5 to Term 6: 128 - 64 = 64
- Growth from Term 6 to Term 7: 256 - 128 = 128
- Growth from Term 7 to Term 8: 512 - 256 = 256
- Growth from Term 8 to Term 9: 1024 - 512 = 512
For \( g(x) \):
- Growth from Term 1 to Term 2: 22 - 12 = 10
- Growth from Term 2 to Term 3: 32 - 22 = 10
- Growth from Term 3 to Term 4: 42 - 32 = 10
- Growth from Term 4 to Term 5: 52 - 42 = 10
- Growth from Term 5 to Term 6: 62 - 52 = 10
- Growth from Term 6 to Term 7: 72 - 62 = 10
- Growth from Term 7 to Term 8: 82 - 72 = 10
- Growth from Term 8 to Term 9: 92 - 82 = 10
Analyze the Statements
-
Statement #1: "While the growth rate of \( g(x) \) is initially greater than the growth rate of \( f(x) \), the growth rate of \( f(x) \) keeps increasing and eventually surpasses the growth rate of \( g(x) \)."
- This statement is false because the initial growth of \( g(x) \) is \( 10 \), while the initial growth of \( f(x) \) is \( 4 \). However, \( f(x) \) does increase and eventually surpasses \( g(x) \) in growth rate.
-
Statement #2: "The growth rate of \( g(x) \) is greater than the growth rate of \( f(x) \) between the second term and the fifth term."
- Between the second term (growth of \( f(x) = 8 - 4 = 4 \)) and the fifth term (growth of \( f(x) = 64 - 32 = 32 \)), the growth of \( g(x) \) remains consistent at \( 10 \) and thus is greater than \( f(x) \) up until Term 4 (where \( f(x) = 16 \) and \( g(x) = 42 \)). This implies that Statement #2 is true.
-
Statement #3: "While the growth rate of \( f(x) \) is initially greater than the growth rate of \( g(x) \), the growth rate of \( g(x) \) keeps increasing and eventually surpasses the growth rate of \( f(x) \)."
- This statement is false. The growth rate of \( f(x) \) eventually surpasses that of \( g(x) \), not the other way around.
Conclusion
The true statement is Statement #2: "The growth rate of \( g(x) \) is greater than the growth rate of \( f(x) \) between the second term and the fifth term."